A Summary Of Recent Findings On Occupational Lung Disease In US Underground Coal Miners - M. D. Attfield (Society for Mining, Metallurgy & Exploration, 1993)
During 1992 a number of papers were published on aspects of respiratory disease in US underground coal miners. These included reports on trends in prevalence of coal workers' pneumoconiosis, the risks of developing coal workers' pneumoconiosis in relation to dust exposure, and the relationship between lung disease other than pneumoconiosis and dust exposure. The intent of this paper is to provide a summary of the essential findings from these investigations. PREVALENCE AND INCIDENCE OF COAL WORKERS' PNEUMOCONIOSIS Coal workers' pneumoconiosis (CWP) is usually detected in living miners through use of the chest x-ray. Deposits of dust in the lung, and the fibrotic tissue reactions to the dust, are manifested on the x-ray as small and large opacities. These abnormalities are quantified into degrees of severity using a standardized classification scheme (the International Classification of Radiographs of the Pneumoconioses of the International Labour Office). For small opacities, the scheme provides for a four-point scale of abnormality (0, 1, 2, 3), reflecting increasing profusion of the opacities on the x-ray. In this report, category 1 or greater small rounded opacities (CWP 1+) represents the earlier radiographic stages of pneumoconiosis. Large opacities, indicate the later and often disabling stage of pneumoconiosis, usually referred to as progressive massive fibrosis (PMF). Information collected in a national surveillance program for underground coal miners (the Coalworkers' X-ray Surveillance Program (CWXSP)) and a large epidemiologic study (National Study of Coalworkers' Pneumoconiosis (NSCWP)) provide a means to assess trends in CWP prevalence over the years following the reduction in dust levels mandated by the 1969 Federal Coal Mine Health and Safety Act (FCMHSA). These programs are operated by the National Institute for Occupational Safety and Health (NIOSH), and are described in detail in Attfield and Althouse (1992) and Attfield and Castellan (1992). Both studies were divided administratively into distinct time periods, and the results shown here reflect that division. Figure 1 shows the prevalence of CWP 1+ as determined from data from the CWXSP, plotted by time period and years in mining. There is evidence of a temporal reduction in prevalence. (The lack of an obvious decline in the early 1970s may be an artifact arising from use of different versions of the standard classification.) Figure 2 provides information in the same format for PMF, and shows a similar trend [ ]